AUTOBIOGRAPHY: FACTOR OR TESTIMONY? - Silva Bernardes, Erick (LINKSCIENCEPLACE, 2026)
This article discusses briefly the written of José de Alencar and Graciliano Ramos, on “Como e por que sou romancista” (2016) and Infância (2008). We shall examine the ways in which the memorialist narratives from the two authors are hybrid genres, mixing biography, soap opera, story and/or novel, but they enjoy that character typically inventory, namely, the overlays of historical elements to their speeches. We will bring to light, comparatively, possible similarities in the work of Ramos, from the aesthetic traits of writing of Alencar. We shall pay attention to the traditional training of José de Alencar, also show their stylistic differences resulting from provable ideological differences, and their consequent importance to his development as intellectual man who was, comparing his autobiographical discourse with the history of Graciliano Ramos’childhood, narrated on a species of poetry without false idealism or empty hopes.